2018
DOI: 10.3390/molecules23051073
|View full text |Cite
|
Sign up to set email alerts
|

Xiaoyaosan Improves Depressive-Like Behaviors in Mice through Regulating Apelin-APJ System in Hypothalamus

Abstract: Background: The apelin-APJ system has been considered to play a crucial role in HPA axis function, and how the traditional Chinese compound prescription Xiaoyaosan regulates the apelin-APJ system as a supplement to treat depressive disorders. Objective: To investigate the depression-like behaviors and expression of apelin and APJ in hypothalamus of chronic unpredictable mild stress (CUMS) mice and study whether these changes related to the regulation of Xiaoyaosan. Methods: 60 adult C57BL/6J mice were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…Moreover, the HPA axis and brain-derived neurotrophic factor (BDNF) have also been widely studied in the context of pathogenesis and treatment of depressive disorders (Jiang et al, 2016). Previous studies have demonstrated that XYS could reverse chronic stress-induced anxiety-like symptoms by regulating the apelin-APJ system in the hypothalamus and activity of the HPA axis (Yan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the HPA axis and brain-derived neurotrophic factor (BDNF) have also been widely studied in the context of pathogenesis and treatment of depressive disorders (Jiang et al, 2016). Previous studies have demonstrated that XYS could reverse chronic stress-induced anxiety-like symptoms by regulating the apelin-APJ system in the hypothalamus and activity of the HPA axis (Yan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to CUMS, which utilizes a battery of different stressors over a time course of several weeks, relatively consistently led to decreases in food intake (Patterson et al, 2010;Yao et al, 2016;He et al, 2018;Yan et al, 2018) and body weight in mice and rats (Forbes et al, 1996;Harris et al, 1997;Patterson et al, 2010;Lopez Lopez et al, 2018;Simas et al, 2018;Yan et al, 2018;Li et al, 2019;Yun et al, 2020). A few studies reported decreases in body weight or body weight gain, while food intake was not significantly altered (Harris et al, 1997;Lopez Lopez et al, 2018;Simas et al, 2018).…”
Section: Effects Of Stress On Food Intake and Body Weight In Rodents mentioning
confidence: 99%
“…In line with this notion, several of the previously mentioned studies also evaluated sucrose or saccharine preference. Some found no differences (Forbes et al, 1996;Harris et al, 1997;Yun et al, 2020), but in several studies CUMS exposure led to reduced sucrose or saccharine intake (Yao et al, 2016;Huang et al, 2017;He et al, 2018;Yan et al, 2018), which may reflect stress-induced anhedonia.…”
Section: Effects Of Stress On Food Intake and Body Weight In Rodents mentioning
confidence: 99%
“…APJ and apelin are distributed in the hypothalamic nuclei, especially in the supraoptic nucleus and paraventricular nucleus (PVN; De Mota et al, ; Pope, Roberts, Lolait, & O'Carroll, ). Studies have suggested that the apelin/APJ system plays a role in regulating the activity of the hypothalamic–pituitary–adrenal axis (Kagiyama et al, ; Yan et al, ). Moreover, the apelin/APJ system affects behavior and physiology in the brain.…”
Section: Agonists Of Apjmentioning
confidence: 99%